ANALISIS PERLAKUAN AKUNTANSI TENTANG AKAD RAHN UNTUK PEMBIAYAAN ARRUM BERDASARKAN PSAK NO 107 DAN FATWA DSN MUI NO 26 PADA PEGADAIAN SYARIAH CABANG LANDUNGSARI MALANG - Shofiyana, Haris (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The concept which is far from riba (usury) and is corresponding with Islamic Law makes the Islamic Mortgage Institution is demanded by some people, especially the middle-lower class society because of the requirements are easy to be fulfilled, accessible and can be done with a relatively short time. With the easiness to obtain loan capital in the form of funds for customers who own a business or run a business by mortgaging his property in the form of gold or diamonds. One of the Islamic Mortgaging Institution's products that provide loan financing to customers engaged in business is gold Arrum Financing with the installment payment system which is conforming with Sharia principles. The purpose of this research is to know how Accounting Treatment of Rahn's Contract (Akad Rahn) for Arrum Financing Based On PSAK 107 and Decree of DSN MUI at Islamic Mortgage Institution Branch Landungsari Malang. This research is design as qualitative method with using descriptive approach. This research is done by three stages, (1) data collection is done by interview, observation, documentation, and online data searching (2) data analysis technique, (3) data analysis with data reduction procedures, data presentation, and conclusion. The results of this study indicate that the Islamic Mortgage Institution of Landungsari Malang about Rahn's contract for Arrum Financing has implemented accounting guidance of PSAK 107 and has been in accordance with the application of Decree of Dewan Standar Nasional Nasional Majlis Ulama Indonesia No.26 / DSN-MUI / III / 2002.